Comparative study of fire resistance and acoustic performance of ceramic brick walls in concern to NBR 15575 in residential buildings in Brazil (2018)
After the publication of NBR 15575 (ABNT, 2013) standard, it became necessary that the constructive systems used in residential buildings go through verification processes concerning the performance requirements. Considering the security requirements, it is necessary to evaluate the fire resistance of vertical sealing systems. Within the scope of habitability, the standard specifies that these systems must have an adequate acoustic performance. Regarding this scenario, this study has the purpose of evaluate the performance of two non-structural vertical sealing systems in ceramic bricks by comparing two different layouts of horizontal air gaps. Therefore, laboratory tests were performed, following the prescriptions of NBR 10636 (ABNT, 1989) and ISO 10140-2 (ISO, 2010). It was verified that the system with higher air gaps number had a better performance on fire resistance, and that the acoustic performance was very similar between the two systems.